The Socio-Economic Factors that Affect Utilisation of Health Care Services by the Exempt Groups Under the National Health Insurance Scheme in Ghana - Yeboah-Mensah, M. (University of Ghana, 2015)
Health financing has become a topical issue among development practitioners in most developing countries. This has necessitated some countries introducing social health insurance schemes as a way of financing health. Health insurance schemes are recognized as a tool to finance health care provision in developing countries including Ghana. The health insurance scheme was introduced in Ghana with the purpose of reducing catastrophic health expenditures, improving access and also ensuring equity in health service delivery. The beneficiaries of the NHIS include informal sector workers, Social Security and National Insurance Trust (SSNIT) contributors, SSNIT pensioners, children under 18 years, pregnant women, the aged (70 years & above) and the indigent (core poor). Among these categories of people, the scheme provides exemption packages for some of them such as children below 18 years, pregnant women, the indigent, SSNIT pensioners, SSNIT contributors and older people (above 70 years). Using secondary household data collected within the three ecological zones in Ghana as well as data from qualitative interviews conducted, this study investigated two categories of the exempt group – those below 18 years and those above 70 years, to unravel some of the socio-economic factors that influence utilization of health care services. The results of both the regression analysis and the focus group discussions suggest the toddlers (0-5 years) and the very old (80+) utilize health care more than the other age groups. Besides, although these groups are exempted from paying premium, some still pay premiums and also make out of pocket (OOP) payments at the health facilities. The results seem to confirm the outcome of several studies on Ghana which identified inequality in the payment of premium and OOP payments. Therefore, an efficient monitoring and supervision on the part of NHIA of the various schemes is recommended while a critical examination of the extent of OOP at the service delivery facilities is suggested.
Thesis(MPhil)-University of Ghana, 2015
Keywords: Socio-Economic Factors; Health Care Services; National Health Insurance Scheme; Ghana